2004
DOI: 10.1007/bf02345210
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial tissue motion influence on laser Doppler perfusion monitoring using tissue Doppler imaging

Abstract: Tissue motion of the beating heart generates large movement artifacts in the laser Doppler perfusion monitoring (LDPM) signal. The aim of the study was to use tissue Doppler imaging (TDI) to localise intervals during the cardiac cycle where the influence of movement artifacts on the LDPM signal is minimum. TDI velocities and LDPM signals were investigated on three calves, for normal heartbeat and during occlusion of the left anterior descending coronary artery. Intervals of low tissue velocity (TDIint, < 1 cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In addition, the laser Doppler signal is mainly influenced by hemoglobin during end diastole. The influence of myoglobin on the Doppler shift during end diastole is negligible [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the laser Doppler signal is mainly influenced by hemoglobin during end diastole. The influence of myoglobin on the Doppler shift during end diastole is negligible [13].…”
Section: Discussionmentioning
confidence: 99%
“…Our laser Doppler system utilized a nontraumatic probe position on the surface of the myocardium in combination with an LVP signal to allow triggered measurements end‐diastolically to avoid confounding artifacts caused by myocardial tissue movements [13,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using echocardiographic tissue Doppler imaging (TDI) indicate reduced tissue velocity in the myocardial wall in relation to late systole and late diastole [3], [4]. A study performed by our group on the beating calf heart using both LDPM and TDI demonstrated intervals with low tissue velocity of the left anterior myocardial wall at late systole and late diastole [5], [6]. During these intervals a stable laser Doppler signal was recorded during normal blood flow conditions.…”
Section: Introductionmentioning
confidence: 97%
“…Previous animal studies with optical measurements in myocardial and brain tissue have shown a potential for using LDF to study the microvascular perfusion [8][9][10]. Currently the techniques are being adapted for human studies together with research and in close collaboration with clinics for different interventions and treatments.…”
Section: Abbreviationsmentioning
confidence: 99%